Preparation method of coring composite material with water ice lunar soil drilling bearing and flexible sealing functions

By using high-performance aromatic heterocyclic organic fibers and nano-aromatic heterocyclic organic fibers combined with high-low temperature-resistant resin materials in the core material of lunar soil, the problems of airtightness and stability in extreme environments are solved. Achieve high-performance lunar soil permafrost sampling material.

CN119320560AInactive Publication Date: 2025-01-17HARBIN INST OF TECH
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411855803.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-17
Publication Date
2025-01-17
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The existing lunar soil core material is difficult to maintain airtightness under extremely high vacuum and high and low temperature environments, resulting in the escape of frozen ice and fine soil, which cannot meet the high airtight, flexibility and stability performance requirements.

Method used

High-performance aromatic heterocyclic organic fibers and nano-aromatic heterocyclic organic fibers combine high- and low-temperature-resistant resin materials to construct a composite material with a multi-gradient hierarchical structure. Through radiation treatment and functional group matching technology, the surface inertia of the material is improved, the pore structure is adjusted, and the gas is enhanced. Tightness and mechanical properties.

Benefits of technology

It realizes the high airtightness and flexibility of lunar soil materials in extreme environments, prevents the escape of frozen ice and fine soil, meets the performance requirements of the "Moon Exploration Fourth Phase" frozen soil sampling task, and provides high-performance lunar soil installation Core extraction material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119320560A_ABST
    Figure CN119320560A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of a coring composite material with water-ice lunar soil drilling bearing and flexible sealing functions, nano heteroaromatic fibers and heteroaromatic organic fibers of different sizes are compounded more tightly through surface grafting and functional group bonding, and the characteristics that the length-diameter ratio of a nano fiber structure is high, the length-diameter ratio of the nano fiber structure is large, and the length-diameter ratio of the nano fiber structure is large are utilized; the lunar soil containing material has the characteristics of high porosity and high surface activity, a supporting layer is constructed between the aromatic heterocyclic organic fiber soft bags, the defects that a current traditional lunar soil containing material is too large in porosity and internal fine soil is lost are overcome, and meanwhile the lunar soil containing material is endowed with more excellent mechanical performance; the composite lunar soil containing material has the advantages that strong guarantee is provided for use of the lunar soil containing material under extremely cold conditions, meanwhile, a compact layer is further constructed on the surface of the soft bag, escape of fine soil and frozen ice is effectively organized, the function of the composite lunar soil containing material is further enhanced on the basis of keeping original flexibility and high-strength performance, the method is simple, and the effect is obvious.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of preparation of core sampling composite materials for lunar soil collection and storage, and specifically relates to a preparation method of a highly airtight aromatic heterocyclic organic fiber composite lunar soil storage and core sampling material. Background Art

[0002] The exploration of lunar polar resources, especially the content and distribution of water resources, is one of the important scientific goals of lunar exploration, which is of great significance to the subsequent deep space exploration and the establishment of lunar scientific research stations. At present, many countries in the world have cooperated to explore the composition of lunar soil. According to my country's lunar exploration plan, the "Lunar Exploration Phase IV" will sample the water-containing lunar soil near the South Pole of the Moon, and the ultimate goal will be to return to Earth in the form of frozen soil and water ice. As one of the core technologies of lunar exploration sampling, the cored lunar soil container material is responsible for collecting lunar soil and ensuring its composition and layered structure. Its performance plays a decisive role in the success of the lunar exploration sampling mission. At present, based on the lunar soil container coring material of the "Chang'e 5" lunar exploration phase III, the "Lunar Exploration Phase IV" coring material also requires high airtightness. However, in the harsh environment of the lunar surface, especially in the high vacuum, high and low temperature coupling environment (below -110℃, the highest is -60℃), most of the airtight materials have problems of crystallization, hardening, breaking and falling off, which makes it difficult to meet the performance requirements of high flexibility, high airtightness, high stability, high flexibility and high strength of the soft bag. At the same time, the inert surface of the "Chang'e 5" lunar soil coring material increases the difficulty of compounding it with airtight materials. Therefore, the development of a new type of highly airtight and flexible composite system is of great scientific and practical significance for the construction of high-performance composite lunar soil coring materials for the "Lunar Exploration Phase IV". Summary of the invention

[0003] The purpose of the present invention is to solve the defect that the lunar soil containing coring materials are too large to preserve fine soil and moisture in the current extreme service environment. A method for preparing a highly airtight composite aromatic heterocyclic organic fiber lunar soil containing coring material is provided, which provides important basic theoretical basis and technical support for the design and development of highly airtight coring materials for lunar soil containing coring materials required for frozen soil sampling in my country's "Lunar Exploration Phase IV".

[0004] The present invention is based on high-performance aromatic heterocyclic organic fiber lunar soil coring material, and uses high and low temperature resistant resin material to seal the void structure of the lunar soil coring material to prevent ice from escaping in a high vacuum environment; homogeneous nano aromatic heterocyclic organic fiber is used to adjust the pore structure of the lunar soil coring material, enhance the support for the airtight material, and then innovatively construct a multi-gradient hierarchical structure of "woven layer (aromatic heterocyclic organic fiber coring material) / support layer (nano aromatic heterocyclic organic fiber) / airtight layer (high and low temperature resistant airtight resin)" soft airtight composite lunar soil coring material. It provides an important basic theoretical basis and technical support for the design and development of coring soft bags required for lunar soil frozen soil sampling in the lunar polar region of my country's next stage of "lunar exploration phase 4".

[0005] To achieve the above purpose, the technical solution adopted by the present invention is as follows: A method for preparing a coring composite material with both water ice and lunar soil drilling bearing and flexible sealing functions, the specific steps are: Step 1: Surface activation and functional group matching treatment of aromatic heterocyclic organic fiber coring materials use 60 Co is the radiation source, and the activity of the radiation source is 3×10 4 Ci. The cleaned aromatic heterocyclic organic fiber core material is placed in a special irradiation bottle and filled with nitrogen to remove oxygen in the bottle. The nitrogen-filled and sealed sample bottle is placed in the irradiation field, and the irradiation dose is 600kGy and the irradiation dose rate is 6kGy.h by calculating the distance between it and the irradiation source and the irradiation time. -1 Aromatic heterocyclic organic fiber coring material.

[0006] Wrap the irradiated grafted heterocyclic organic fiber core material (0.5 m) on a glass frame and place it in a 1L beaker. Inject 800 mL of 2% mass fraction silane coupling agent (including: chain length of silane coupling agent, type of functional group, etc.) / ethanol solution into it. Under magnetic stirring, react at 70 ° C for 4 hours. After the reaction, take out the fiber, rinse it repeatedly with anhydrous ethanol, and finally dry it at 110 ° C for 1 hour to obtain heterocyclic organic lunar soil containing materials grafted with different silane coupling agents.

[0007] Step 2: Preparation method of nano aromatic heterocyclic organic fibers of different sizes Under nitrogen protection and stirring, adding a polymerization aid calcium chloride and a surfactant polyvinyl pyrrolidone to N-methyl pyrrolidone, heating to completely dissolve it, then using an ice water bath to reduce the system temperature to 5°C, adding p-phenylenediamine, and adding terephthaloyl chloride after it is completely dissolved, and maintaining high-speed stirring, the stirring rate is 1500 r / min for polymerization, and the ice water bath is maintained during the polymerization process to maintain the system temperature not exceeding 50°C. After the polymerization reaction is completed, N-methyl pyrrolidone solvent is added to the reaction solution, and the polymer is evenly dispersed by a high-speed homogenizer, the speed of the high-speed homogenizer is 8000 r / min, the homogenization time is 5 min, after uniform dispersion, n-hexane separation agent is added, and the high-speed homogenizer is continued to be homogenized, the speed of the high-speed homogenizer is 6000 r / min, and the homogenization time is 5 min, and finally the homogenized system is filtered, washed, and vacuum dried to obtain nano aromatic heterocyclic organic fibers; Step 3: Preparation of coring material / nano aromatic heterocyclic fiber composite coring material Disperse the nano-aromatic heterocyclic organic fibers prepared in step 2 in ethanol, use a disperser to fully mix and obtain a nano-aromatic heterocyclic fiber solution, spread the lunar soil coring material prepared in step 1 on a tetrafluoroethylene plate, evenly apply the nano-aromatic heterocyclic fiber solution on the lunar soil coring material, scrape off excess nano-aromatic heterocyclic fiber solution on the surface of the lunar soil coring material, and attach the nano-aromatic heterocyclic fiber solution to the fiber gaps of the lunar soil coring material. After the preparation is completed, soak the obtained composite lunar soil coring material in deionized water to remove the ethanol solvent in the nano-aromatic heterocyclic fibers. After the solvent is replaced, dry the composite lunar soil coring material in an oven at 80°C to obtain a dense composite coring material.

[0008] Step 4: Structural control and preparation of highly airtight and high and low temperature resistant composite coring materials for lunar soil The composite coring material prepared in step 3 was soaked in the ethanol solution of silicone rubber. After 10 minutes, it was taken out and spread on the surface of the polytetrafluoroethylene plate, and the excess silicone rubber was evenly scraped off and cured at room temperature. At the same time, the soaked composite coring sleeve was placed on the polytetrafluoroethylene hose to ensure the uniformity of the lunar soil container material.

[0009] Furthermore, in step 1, the radiation source used in the radiation field is 60 Co, the activity of the irradiation source is 3×10 4 Ci.

[0010] Furthermore, in step 1, after irradiation treatment, the irradiation dose is 600 kGy and the irradiation dose rate is 6 kGy.h -1 Aromatic heterocyclic organic fiber coring material.

[0011] Furthermore, in step 1, the silane coupling agent is KH550; the mass fraction of the silane coupling agent is 2%.

[0012] Furthermore, in step 2, the content of polyvinyl pyrrolidone in the N-methylpyrrolidone solution is 0.05-3%.

[0013] Furthermore, in step 2, the diameter of the prepared nano aromatic heterocyclic fiber is 50-150 nm.

[0014] Furthermore, in step three, the lunar soil core material is coated with homogeneous nano-aromatic heterocyclic organic fibers.

[0015] Furthermore, in step three, the coating diameter of the nano aromatic heterocyclic organic fiber ranges from 50 to 150 nm.

[0016] Furthermore, in step 4, the content of organic silicone rubber in the ethanol solution of organic silicone rubber is 2%; and the organic silicone rubber is high and low temperature resistant organic silicone rubber.

[0017] Furthermore, the high and low temperature resistant silicone rubber is any one or more of methyl silicone rubber, vinyl silicone rubber, and phenyl silicone rubber.

[0018] The beneficial effects of the present invention compared to the prior art are: 1. The harsh environment on the lunar surface, especially in the high vacuum, high and low temperature coupling environment (below -110℃, the highest is -60℃), most of the airtight materials have problems of crystallization, hardening, breaking and falling off, which makes it difficult to meet the performance requirements of high flexibility, high airtightness and high stability of soft bags. As a high molecular polymer material with both organic and inorganic characteristics, silicone rubber shows extremely excellent high and low temperature resistance. It is the material with the widest temperature range in rubber resin at present. It maintains certain physical and mechanical flexibility in a fairly wide temperature range (-120℃-300℃). Therefore, silicone rubber (including: vinyl silicone rubber; methyl silicone rubber; phenyl silicone rubber) is used to coat the surface of the lunar soil material, which improves its airtightness and prevents fine soil and frozen ice from escaping in the harsh environment of outer space. At the same time, it ensures that the composite lunar soil material maintains high flexibility under extremely low temperature conditions on the lunar surface, thereby ensuring the normal use of the lunar soil material in the harsh environment of the lunar shadow area.

[0019] 2. At present, the use of polymer sealing materials to densely contain lunar soil coring materials is still difficult to meet the required performance requirements. The main reason is that under high vacuum environment, the weak physical and mechanical properties of polymer resins make it easy to expand and deform in the large pore structure (pore size: 20μm) inside the lunar soil coring materials due to the lack of effective mechanical support, which makes the composite coring materials ineffective. Nano aromatic heterocyclic organic fibers are homogeneous materials with the same structure as traditional organic fibers. In view of the successful demonstration in the early stage, they can also overcome the harsh environment of the lunar surface and eliminate the risks brought by the unstable performance of supporting materials. At the same time, due to the significant reduction in the size of nanofibers (50nm-150nm), the assembled fiber film has an extremely small pore structure (less than 1.0-10 nm), which can significantly improve the stability of the airtight material in the pores. Therefore, the use of homogeneous nanomaterials of different sizes to adjust the pore structure of aromatic heterocyclic organic fiber coring materials for lunar soil, enhance the support of the airtight resin material inside the pores of the coring material, and realize the preparation of highly airtight soft high and low temperature resistant composite materials for lunar soil.

[0020] 3. The inert surface structure of traditional aromatic heterocyclic organic fibers greatly increases the difficulty of compounding with airtight materials, making it difficult for composite lunar soil-containing composite materials to fully exert their theoretical expected performance. The present invention starts with precise interface design and matching, and uses irradiation (gamma-ray irradiation, plasma irradiation) combined with precise matching of functional group structures to improve the inert surface of coring materials, and explores the interface matching and interaction mechanism between coring materials with different surface micro-area structures and airtight materials. Through precise structural optimization, the active site density, group chain length, molecular chain rigidity and flexibility, and inter-chain interactions are regulated to clarify the influence of the interface structure evolution between the two on their mutual adhesion stability, thereby laying the foundation for improving the performance of composite coring materials for the "Lunar Exploration Phase IV".

[0021] 4. The composite coring soft bags for the "Lunar Exploration Phase IV" need to have the characteristics of light weight, high flexibility at low temperature, high airtightness in vacuum, puncture resistance and high stability in drilling and mining, but these factors are contradictory and restrictive. Therefore, coordinating the intrinsic relationship between these characteristic factors and clarifying the influence of changes in the structure of airtight composite materials on the comprehensive performance of composite coring materials for containing lunar soil are the key to high-performance composite coring materials for containing lunar soil. The present invention constructs an airtight composite system (nanoaromatic heterocyclic organic fibers and high and low temperature resistant airtight resin materials) through collaborative design, explores the influence of the structural evolution of airtight composite materials on the low temperature flexibility, high vacuum airtightness and drilling and mining structural stability of composite coring soft bags in extreme drilling and mining service environments. By regulating nano-aromatic heterocyclic organic fibers (loading, size), high and low temperature resistant and flexible airtight resin materials (type, molecular weight, cross-linking density, branch type and ratio, loading), etc., combined with the evaluation of drilling and production performance under complex working conditions and simulation of the mechanical characteristics of airtight composite materials inside the soft bag aperture, we can fully understand the influence of composite coring soft bags with different structures / morphologies and surface / interface properties on their comprehensive performance and their mechanism of action, so as to achieve light weight and high flexibility, which provides important theoretical basis and technical support for the design and preparation of composite coring soft bags for the "Lunar Exploration Phase IV".

[0022] 5. The manufacturing process of this embodiment is simple and the preparation is convenient. The parameters such as aromatic heterocyclic organic fibers, nano aromatic heterocyclic organic fibers (size, content), and airtight materials (type, content) are highly adjustable and have high practical value. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] The accompanying drawings are used to provide further explanation of the present invention and constitute a part of the specification. Together with the embodiments of the present invention, they are used to explain the present invention and do not constitute a limitation of the present invention. In the accompanying drawings: Figure 1 : Example 1 Design route map of composite lunar soil containing composite coring soft bag; Figure 2 : Example 1 Aromatic heterocyclic organic fiber lunar soil containing coring material; Figure 3 : Example 1 Schematic diagram of surface treatment of aromatic heterocyclic organic fibers; Figure 4 : Example 1 SEM images of nano aromatic heterocyclic organic fibers of different sizes; Figure 5 : Photographs of surface structure regulation of composite coring material in Example 1; Figure 6 : Photograph of the structural changes of the composite coring material after nanofiber coating in Example 1; Figure 7 : Example 1 Wetting performance characterization; Figure 8 : Pictures of coring material and composite coring material in Example 1; Pictures of water retention experiment; Fig. 9 : Pictures of coring material and composite coring material before and after the vibration test in Example 1; Fig.10 : Example 1: Ice retention rate of coring material and composite coring material under vacuum environment. DETAILED DESCRIPTION

[0024] The technical solution of the present invention is further described below in conjunction with the accompanying drawings and embodiments, but is not limited thereto. Any modification or equivalent replacement of the technical solution of the present invention that does not depart from the spirit and scope of the technical solution of the present invention should be included in the protection scope of the present invention.

[0025] By irradiating the fibers of the aromatic heterocyclic organic fiber coring material, the inertia of the fiber surface is improved, and the high-strength combination of the aromatic heterocyclic organic fiber coring material and the airtight material is achieved through the precise compounding of the functional group structure. Compared with the traditional aromatic heterocyclic organic fiber, the homogeneous material of the nano aromatic heterocyclic organic fiber and the aromatic heterocyclic organic fiber in the present invention not only inherits the high strength, high modulus, and high temperature resistance of the traditional aramid fiber, but also greatly reduces the size. At the same time, the present invention adopts nano aromatic heterocyclic fibers of different scales to achieve the precise adjustment of the void structure of the lunar soil coring material, effectively preventing the escape of fine soil. In addition, by introducing high and low temperature resistant resin-based materials to further compact the lunar soil coring material, the compactness of the material is improved, the porosity of the lunar soil coring material is reduced, and the escape of frozen fine soil in a high vacuum environment is prevented. The assembled soft bag has very excellent tensile properties and flexibility. It provides a scheme reference and technical support for the collection of lunar frozen soil and the demonstration of moisture content and engineering implementation of my country's "Moon Exploration Phase IV" mission.

[0026] Figure 1 The design roadmap of the composite lunar soil containing composite coring soft bag of Example 1 of the present invention is as follows: 1. Use gamma-ray irradiation to graft aromatic heterocyclic fibers to improve the chemical inertness of the fiber surface, and use silane coupling agent functional group matching to achieve a high degree of interface bonding between the lunar soil containing coring material and the airtight material. 2. Use polymerization induced dispersion method to prepare nano aromatic heterocyclic organic fibers with different aspect ratios. 3. Evenly coat the nano aromatic heterocyclic organic fibers on the surface of the lunar soil containing material to make up for and fill the defect of the excessively large pore size of the coarse fiber lunar soil containing material and improve the strength of the airtight layer material. 4. Evenly coat the silicone rubber on the surface of the lunar soil containing material to enhance the low temperature resistance of the lunar soil containing material and further enhance the airtightness of the lunar soil containing material, and finally prepare a highly airtight aromatic heterocyclic fiber composite lunar soil containing material with uniform performance, dense structure and homogeneity.

[0027] Example 1 A method for preparing a coring composite material having both water ice and lunar soil drilling bearing and flexible sealing functions comprises the following steps: Step 1: Surface activation and functional group matching treatment of aromatic heterocyclic organic fiber coring materials The surface of the lunar soil coring material is activated and modified by taking advantage of the strong penetrating power of gamma rays, simple operation, and the ability to modify the entire surface of large-sized samples, thereby expanding the subsequent surface modification space of the coring material and inducing cross-linking of microfibers inside the fiber, improving the bonding strength of the fiber core, and achieving integrated modification of the fiber body strength and surface activation. Based on the research foundation of Chang'e 5, a soft aromatic heterocyclic organic fiber lunar soil coring material ( Figure 2 ).use 60 Co is the radiation source, and the activity of the radiation source is 3×10 4 Ci. The cleaned aromatic heterocyclic organic fiber core material is placed in a special irradiation bottle and filled with nitrogen to remove oxygen in the bottle. The nitrogen-filled and sealed sample bottle is placed in the irradiation field, and the irradiation dose is 600kGy and the irradiation dose rate is 6kGy.h by calculating the distance between it and the irradiation source and the irradiation time. -1 . Place the irradiated grafted coring material (length 0.5m) in a 1L beaker. Inject 800mL of 2% by mass silane coupling agent / ethanol solution into it. Under magnetic stirring, react at 70°C for 4h. After the reaction, take out the fiber, rinse it repeatedly with anhydrous ethanol, and finally dry it at 110°C for 1h to obtain the preparation of the coring material modified by silane coupling agent grafting. At the same time, by adjusting the type and chain length of the injected silane coupling agent, the lunar soil-filled coring material of high-performance aromatic heterocyclic organic fibers with different functional groups and different chain grafting lengths is obtained. The preparation schematic diagram is shown below. Figure 3 shown.

[0028] Step 2: Preparation method of nano aromatic heterocyclic organic fibers of different sizes Add 100 ml of N-methylpyrrolidone to a 250 mL three-necked flask, add 5 g of polymerization aid calcium chloride and 0.05 g of surfactant polyvinylpyrrolidone under nitrogen protection and stirring, and heat to 100 °C to completely dissolve them. Then use an ice-water bath to cool the system to 5 °C and add 2.0 g of p-phenylenediamine. After it is completely dissolved, add 4.0 g of terephthaloyl chloride and maintain high-speed stirring (1500 r / min) for polymerization. Keep an ice-water bath during the polymerization process to maintain the system temperature at no more than 50 °C. After 1.5 h of reaction, stop the reaction. Then add 200 mL of N-methylpyrrolidone solvent to the reaction solution, and use a high-speed homogenizer to evenly disperse the polymer solution at a speed of 8000 r / min and a stirring time of 5 min. After uniform dispersion, add 200 ml of n-hexane separation agent to the above mixed solution, set the speed of the high-speed homogenizer to 6000 r / min, and homogenize for 5 min. Filter the homogenized system and obtain nanofibers. The obtained aramid nanofibers were washed and filtered three times with ethanol and deionized water, and finally the filtered products were dried in a vacuum drying oven at 60 °C for 24 h to obtain nano aromatic heterocyclic organic fibers, such as Figure 4 shown.

[0029] Step 3: Preparation of coring material / nano aromatic heterocyclic fiber composite coring container material Disperse 0.5 g of the nano-aromatic heterocyclic organic fibers prepared in step 2 in 99.5 g of ethanol and mix thoroughly using a disperser. Then, soak the 20 cm long and 2.72 cm wide aromatic heterocyclic fiber lunar soil container material in the mixture ( Figure 2 ). After 10 minutes of infiltration, take out the composite lunar soil container material, and spread the lunar soil container material on the surface of the polytetrafluoroethylene plate. After spreading, evenly infiltrate the nano-aromatic heterocyclic fiber solution. At the same time, put the infiltrated composite coring sleeve on the polytetrafluoroethylene hose to ensure the uniformity inside the lunar soil container material. After uniform infiltration and coating, soak the composite lunar soil container material in deionized water to remove the solvent in the nanofiber solution and wash it repeatedly for 3-5 times. After the ethanol is completely removed, dry it in an oven at 100°C for 1 hour. The preparation of coring material / nanofiber composite coring material is achieved through the interaction of functional groups between nanofibers and modified coring materials, such as Figure 5 As shown in the figure, it can be clearly observed that the nanofibers are attached to the coring material. At the same time, due to the repair of the nanofibers, the void structure is added and greatly reduced compared with the initial coring material, which lays a good foundation for the preparation of dense composite coring materials, such as Figure 6 In addition, due to the hydrophobic properties of the nanofiber membrane, it is difficult for water to penetrate, further preventing the escape of water, as shown in Figure 7 shown.

[0030] Step 4: Structural control and preparation of highly airtight and high and low temperature resistant composite coring materials for lunar soil For highly airtight soft composite coring materials, the selection of high and low temperature resistant resins also plays a key role. The lunar soil containing material coated with nano aromatic heterocyclic fibers of different sizes in step 3 is soaked in a 2% organic silicone rubber (vinyl silicone rubber) ethanol solution. After 10-30 minutes, the lunar soil containing material is taken out and spread on the surface of the polytetrafluoroethylene plate to fully soak the organic silicone rubber and remove excess material. At the same time, the soaked composite coring sleeve is placed on the polytetrafluoroethylene hose to ensure the uniformity of the interior of the lunar soil containing material. After uniform coating, it is cured at room temperature of 25°C for 0.5h to finally obtain a homogeneous, flexible and highly airtight composite coring material.

[0031] The results show that the initial coring material contains a large number of pores on the surface, such as Figure 6 As shown in the figure, it is difficult to retain liquid water. In contrast, the airtight composite coring material basically fills the pores of the "Chang'e 5" coring material, and the water is retained, making it difficult to penetrate. Figure 8 At the same time, after the strong vibration test, a large amount of fine soil escaped from the initial coring material and remained on its surface, while the surface of the coring material of the composite coring material remained basically unchanged before and after vibration, as shown in Figure 2. Fig. 9 As shown. In addition, in the high vacuum frozen ice volatilization escape experiment, the frozen ice content inside the initial coring material decreases rapidly with time. In contrast, due to the high airtightness and stability of the airtight composite coating in a vacuum environment, the composite coring soft bag can effectively retain the frozen ice for a long time and prevent it from escaping, as shown in the figure. Fig.10 shown.

[0032] The present invention achieves a tighter compound between nano aromatic heterocyclic fibers and aromatic heterocyclic organic fibers of different sizes through surface grafting and functional group bonding. By utilizing the high aspect ratio and high surface activity of the nanofiber structure, a support layer is constructed between the soft bags of aromatic heterocyclic organic fibers to make up for the defects of the current traditional lunar soil containing materials, such as excessive porosity and internal fine soil loss. At the same time, the lunar soil containing materials are given more excellent mechanical properties. The coating of organic silicone rubber provides a strong guarantee for the use of the lunar soil containing materials in extremely cold conditions. At the same time, a dense layer is further constructed on the surface of the soft bag to effectively organize the escape of fine soil and frozen ice. On the basis of maintaining the original flexibility and high strength performance, the function of the composite lunar soil containing materials is further enhanced. The method is simple and the effect is obvious.

[0033] Finally, it should be noted that the above-mentioned embodiments only express several implementation methods of the present invention and are not intended to limit the invention. For those skilled in the art, any modification, equivalent replacement, improvement, etc. made without departing from the concept of the present invention should be included in the protection scope of the invention. Therefore, the protection scope of the patent of the present invention shall be subject to the attached claims.

Claims

1. A method for preparing a coring composite material with both water ice and lunar soil drilling bearing and flexible sealing functions, characterized in that: The method comprises the following steps: Step 1: Surface activation and functional group matching treatment of aromatic heterocyclic organic fiber coring materials: The cleaned heterocyclic organic fiber coring material is placed in a special irradiation bottle, and after nitrogen filling and sealing, the sample bottle is placed in an irradiation field for irradiation treatment; the irradiated heterocyclic organic fiber coring material is placed in a silane coupling agent / ethanol solution, and under the action of magnetic stirring, the heat preservation reaction is carried out. After the reaction is completed, the heterocyclic organic fiber coring material is repeatedly rinsed with anhydrous ethanol and dried to obtain the high-performance heterocyclic organic fiber lunar soil coring material; Step 2: Preparation of nano aromatic heterocyclic organic fibers: Under nitrogen protection and stirring, adding a polymerization aid calcium chloride and a surfactant polyvinyl pyrrolidone to N-methyl pyrrolidone, heating to completely dissolve it, then using an ice water bath to reduce the system temperature to 5°C, adding p-phenylenediamine, adding terephthaloyl chloride after it is completely dissolved, and maintaining high-speed stirring to polymerize, maintaining an ice water bath during the polymerization process, and maintaining the system temperature not exceeding 50°C, after the polymerization reaction is completed, adding N-methyl pyrrolidone solvent to the reaction solution, and using a high-speed homogenizer to evenly disperse the polymer, adding n-hexane separating agent, and continuing to use the high-speed homogenizer for homogenization, and finally filtering the homogenized system, washing, and vacuum drying to obtain nano aromatic heterocyclic organic fibers; Step 3: Preparation of coring material / nano aromatic heterocyclic organic fiber composite coring container material: The nano-aromatic heterocyclic organic fibers prepared in step 2 are dispersed in ethanol to obtain a nano-aromatic heterocyclic fiber solution. The lunar soil core material prepared in step 1 is spread on a tetrafluoroethylene plate, and the nano-aromatic heterocyclic fiber solution is evenly coated on the lunar soil core material. The excess nano-aromatic heterocyclic fiber solution on the surface of the lunar soil core material is scraped off, and the nano-aromatic heterocyclic fiber solution is attached to the fiber gaps of the lunar soil core material. After the preparation is completed, the obtained composite lunar soil core material is immersed in deionized water to remove ethanol, and dried to obtain a dense composite core material. Step 4: Structural control and preparation of highly airtight and high and low temperature resistant composite coring materials for lunar soil: Immerse the dense composite coring material prepared in step three into the ethanol solution of silicone rubber, take it out and spread it flat to fully soak the silicone rubber, scrape off excess silicone rubber, and cure it at room temperature to obtain a coring composite material with both water ice and lunar soil drilling bearing capacity and flexible sealing functions.

2. The method for preparing a coring composite material having both water ice and lunar soil drilling bearing and flexible sealing functions according to claim 1, characterized in that: In step 1, the radiation source used in the radiation field is 60 Co, the activity of the irradiation source is 3×10 4 Ci.

3. The method for preparing a coring composite material having both water ice and lunar soil drilling bearing and flexible sealing functions according to claim 1, characterized in that: In step 1, after irradiation treatment, the irradiation dose is 600 kGy and the irradiation dose rate is 6 kGy.h -1 Aromatic heterocyclic organic fiber coring material.

4. The method for preparing a coring composite material having both water ice and lunar soil drilling bearing and flexible sealing functions according to claim 1, characterized in that: In step 1, the silane coupling agent is KH550; the mass fraction of the silane coupling agent is 2%.

5. The method for preparing a coring composite material having both water ice and lunar soil drilling bearing and flexible sealing functions according to claim 1, characterized in that: In step 2, the content of polyvinyl pyrrolidone in the N-methylpyrrolidone solution is 0.05-3%.

6. The method for preparing a coring composite material having both water ice and lunar soil drilling bearing and flexible sealing functions according to claim 1, characterized in that: In step 2, the diameter of the prepared nano aromatic heterocyclic fiber is 50-150 nm.

7. The method for preparing a coring composite material having both water ice and lunar soil drilling bearing and flexible sealing functions according to claim 1, characterized in that: In step three, the lunar soil core material is coated with homogeneous nano-aromatic heterocyclic organic fibers.

8. The method for preparing a coring composite material having both water ice and lunar soil drilling bearing and flexible sealing functions according to claim 1, characterized in that: In step three, the coating diameter of the nano-aromatic heterocyclic organic fiber ranges from 50 to 150 nm.

9. The method for preparing a coring composite material having both water ice and lunar soil drilling bearing and flexible sealing functions according to claim 1, characterized in that: In step 4, the content of the organic silicone rubber in the ethanol solution of the organic silicone rubber is 2%; the organic silicone rubber is a high and low temperature resistant organic silicone rubber.

10. The method for preparing a coring composite material having both water ice and lunar soil drilling bearing and flexible sealing functions according to claim 9, characterized in that: The high and low temperature resistant silicone rubber is any one or more of methyl silicone rubber, vinyl silicone rubber and phenyl silicone rubber.

Citation Information

Patent Citations

  • Surface modified aramid fiber, surface modification method thereof and static sealing material

    CN103194898A

  • Preparation method of p-aramid nanofiber

    CN105153413A

  • Preparation method of compact aramid fiber coring soft bag for preventing fine soil and water from escaping

    CN113445328A

  • Preparation method of high-airtightness fiber composite coring soft bag

    CN117904869A